2020
DOI: 10.1167/iovs.61.8.19
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Inhibition Accelerates Corneal Endothelial Wound Healing through Increased Endothelial Cell Division and Migration

Abstract: To investigate the role of phosphatase and tensin homologue deleted on chromosome 10 (PTEN) in the regulation of corneal endothelial cell (CECs) focusing on proliferation and migration, and to further evaluate the application of PTEN inhibitors in the treatment of corneal endothelial dysfunction in a rat model. METHODS. Expression of PTEN in human and rat corneal endothelium was determined by immunocytochemistry, western blotting, and ELISA. A small molecular inhibitor of PTEN, bpV(pic), was applied in the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For higher transfection efficiency, normal and injured mice corneas were isolated to be organ-cultured as previously described 33 . Ad-GFP (0.5 μL, 1 × 10 10 pfu, Control group) or Ad-PAX6 (0.5 μL, 1 × 10 10 pfu, PAX6 group) was added to the cultured injured corneas.…”
Section: Organ Culturementioning
confidence: 99%
“…For higher transfection efficiency, normal and injured mice corneas were isolated to be organ-cultured as previously described 33 . Ad-GFP (0.5 μL, 1 × 10 10 pfu, Control group) or Ad-PAX6 (0.5 μL, 1 × 10 10 pfu, PAX6 group) was added to the cultured injured corneas.…”
Section: Organ Culturementioning
confidence: 99%
“…47,74 Nuclear accumulation of p27kip1 is caused by the phosphatase and tensin homolog (PTEN) proteininduced inhibition of AKT phosphorylation. 77 Zhang et al showed that inhibition of PTEN results in a stimulation of cell cycle progression as well as an increased migration behavior of CEnCs which emphasize the effect on wound healing. 77 In general, PI3K and Akt modulate cell cycle progression, enhance cell survival, but may also cause EnMT induction with concomitant increase in motility together with aberrant ECM secretion.…”
Section: Resultsmentioning
confidence: 99%
“…PTEN is related to the downregulation of the PI3K/AKT pathway and acts as an anti-tumor gene by mediating the cell cycle, apoptosis, and migration ( 29 ). PTEN inhibition has been demonstrated to accelerate wound healing in corneal endothelia by increasing the division and migration of endothelial cells ( 30 ). MiR-21-mediated inhibition of PTEN activated the PI3K/AKT pathway and contributed to skin wound healing ( 31 ).…”
Section: Discussionmentioning
confidence: 99%